1990
DOI: 10.1017/s0022215100114434
|View full text |Cite
|
Sign up to set email alerts
|

Tympano–cartilago–stapediopexy: a method to improve hearing in open technique tympanoplasty

Abstract: Canal wall-down technique tympanoplasty was indicated in about 41 per cent of our cases with chronic suppurative otitis media. In this series done during the last four years, of 576 tympanoplasties, 240 cases needed type III tympanoplasty. In 145 cases, myringostapediopexy was carried out using temporalis fascia grafting over the head of the stapes. Tympano-cartilago-stapediopexy was performed in the other 95 cases by using tragal cartilage and perichondrium over the stapes. A comparison between the results of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 5 publications
1
11
0
Order By: Relevance
“…Moustafa and Khalifa observed the hearing results of this technique in 95 cases, compared with 145 cases who had undergone simple myringostapediopexy. They showed that 84 per cent of the myringo-cartilage-stapediopexy patients had an ABG of less than 20 dB 11 . Similar results were obtained by Artuso et al , 7 who showed a similar advantage when comparing myringostapediopexy with single-stage ossiculoplasty.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Moustafa and Khalifa observed the hearing results of this technique in 95 cases, compared with 145 cases who had undergone simple myringostapediopexy. They showed that 84 per cent of the myringo-cartilage-stapediopexy patients had an ABG of less than 20 dB 11 . Similar results were obtained by Artuso et al , 7 who showed a similar advantage when comparing myringostapediopexy with single-stage ossiculoplasty.…”
Section: Discussionsupporting
confidence: 65%
“…Myringostapediopexy has been a commonly used repair technique in mastoid surgery for many years 10 , 11 , 16 , 17 . The hearing results after myringostapediopexy in our series therefore make an interesting comparison group.…”
Section: Discussionmentioning
confidence: 82%
“…Moustafa and Khalifa observed hearing results of simple myringostapediopexy technique in (n=145) and showed that only 10% of these cases achieved PTA-ABG closure of less than 30 dB. 11,12 Functional results are often influenced by wide variability in the surgical techniques employed, in the criteria used to evaluate hearing results and a number of other anatomical, physiological and pathological events that occur post-operatively in the middle ear as mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…Shrestha et al, [7] and Cheang and Cho [28] reported ABG closure of 73.7% and 61% within 0-30 db in type III tympanoplasty, while Moustafa and Khalifa [29] observed hearing results of simple myringostapediopexy technique in 145 cases and showed that only 10% of these cases achieved PTA-ABG closure of less than 30 dB.…”
Section: Air Bone Gapmentioning
confidence: 99%